Medieval Afterlives in Popular Culture
XII, 245 p.
Keywords: This book is concerned with our ideological, technical and emotional investments in reclaiming medieval for contemporary popular culture. The authors illuminate both medieval and contemporary popular culture in surprising and productive ways while interrogating the many ways in which metamedievalism reinterprets and reconceptualises the medieval.